Development of Learning Media Using the Lectora Inspire Application for PAI Subjects in Class VIII at SMPN 2 Payakumbuh - Maulid, Muhammad Iqbal; Ilmi, Darul (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
The lack of adequate learning media for Class VIII PAI subjects at SMPN 2 Payakumbuh served as the impetus for this research, as it has adversely affected the overall learning process. To address this issue, the study focused on the development of PAI learning media tailored to Class VIII, ensuring it met validity standards. The objective was to design valid learning media using the Lectora Inspire application for use at SMPN 2 Payakumbuh. This study employed a developmental research approach based on the 4D model, which encompasses four main stages: Define, Design, Develop, and Disseminate. However, this research was confined to the Develop stage. The findings indicate that the learning media achieved validity criteria, as evidenced by its alignment with the CP, TP, and ATP standards, as well as the suitability of its graphics, layout, and typography. Expert validation, conducted by two PAI content specialists and one media expert, rated the quality of the interactive learning media produced using the Lectora Inspire application as